Efficacy of 0.5% Timolol Maleate versus 0.05% Clobetasol Propionate in Treating Superficial Infantile Hemangioma: A Pilot Randomized Controlled Trial - Sunita Singh; Niraj Kumar Srivastava; Amrita Upadhyaya; Mrityunjay Kumar; Neeraj Pawar; Rohit Kapoor (Journal of Indian Association of Pediatric Surgeons)
Aim: To compare the efficacy of two topical agents in superficial infantile hemangioma (SIH). Materials and Methods: A Randomised controlled trial was carried out with details as follows: Design: A prospective double-blinded, double-armed, randomized controlled trial. Setting: Multidisciplinary unit from 2022 to 2024. Subjects: Children younger than 2 years with color Doppler-confirmed SIH (superficial to deep dermal fascia). Methods: Randomization in treatment arm I: topical beta-blocker 0.5% timolol maleate (TTM) solution or treatment arm II: ultrapotent topical Steroid 0.05% clobetasol propionate ointment. Outcome: (1) reduction in area, (2) color change on visual analog scale (VAS), and (3) total VAS scores for color, size, and thickness. Each VAS parameter was rated from 0 to 3 (cumulative score 0–9). Results: Twenty patients were enrolled in each arm. Four patients in each group missed 96 weeks of follow up assessment but completed at least 9 months of treatment. In arm I, two patients were transitioned from TTM to oral propranolol due to rapid progression deep into the dermis. Arm I demonstrated a quicker improvement in color with a steeper reduction in area. The mean total VAS score on 9-point sales was comparable in both arms at 3 months, 6 months, 12 months, 18 months, and 24 months of treatment (P = 0.223, P = 0.123, P = 0.123, P = 0.123, and P = 0.103). At the end of the 96th week, both treatments achieved an excellent response (P = 0.634) with no rebound growth. Conclusion: 0.5%-TTM solution can be a first-line therapy for SIH due to its rapid onset of action and overall comparable efficacy in reducing SIH size. While clobetasol remains effective, its slower response may limit its utility.